Experimental investigation of the flow over IIUM-MAV using six component balance test and particle image velocimetry - Omar, Ashraf Ali; Altaf, Alaman; Azwir, Ahmad Rizal; Abdul Rahman, Mohd Amirul (2011)
The main purpose of this project was to study the aerodynamic performance of IIUM-micro aerial vehicle (IIUMMAV7) using six components balance and flow visualization using PIV system. The experimental model of Micro Air Vehicle (MAV) shaped like cropped delta wing was designed, fabricated and tested in low speed wind tunnel. The surface flow patterns were examined. The experimental work was conducted to measure the aerodynamic forces of lift, drag, pitching moment, side force and normal force coefficients using six components balances at several angles of attack and Reynolds range from 2.30 x 10⁵ to 6.13 x 10⁵. Furthermore, the complex subsonic flow phenomena on the model have been visualized and investigated by using the particle image Velocimetry (PIV). It was found that stall for the MAV occurred between α = 20°-25° and that the MAV performs better that relatively higher speeds. It was also found that the winglets improved the overall stability of the MAV.